1970
DOI: 10.4319/lo.1970.15.4.0625
|View full text |Cite
|
Sign up to set email alerts
|

Currents North of Bering Strait in Winter1

Abstract: Four days of current record were obtained about 190 km NNE of Bering Strait during Mcarch 1968. The mean current was the same for the location as in summer, suggesting that the generally north flow from the Bering Sea to the Arctic Ocean occurs also in winter. Variations in speed and direction of the flow were identified and analyzed. The major periodic variation was due to the diurnal tidal wave, and thus the tidal wave rather than inertial currents must be the primary cause of periodic variations. The course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Ice that passes through eastern Bering Strait follows the isobaths along the Alaska coast past Cape Lisburne toward Barrow Canyon. This division of the ice flow field north of Bering Strait is only approximate, since the variations caused by shifts in the wind regime can shut off the Alaska coastal current [Coachman and Tripp, 1970]. For instance, Thomas and Pritchard [1981] showed that floes passing close to Cape Prince of Wales joined the broad flow toward Wrangel Island as a result of a prolonged period of easterly winds.…”
Section: Discussionmentioning
confidence: 99%
“…Ice that passes through eastern Bering Strait follows the isobaths along the Alaska coast past Cape Lisburne toward Barrow Canyon. This division of the ice flow field north of Bering Strait is only approximate, since the variations caused by shifts in the wind regime can shut off the Alaska coastal current [Coachman and Tripp, 1970]. For instance, Thomas and Pritchard [1981] showed that floes passing close to Cape Prince of Wales joined the broad flow toward Wrangel Island as a result of a prolonged period of easterly winds.…”
Section: Discussionmentioning
confidence: 99%
“…2 & 7) in association with the cold, highly saline, and nutrient-rich (Fig. 9) Anadyr Current that brings nutrients and zooplankton northward from the Bering Sea (Coachman et al 1975, Sambrotto et al 1984, Iken et al 2010). In contrast, the Alaskan Coastal Current that parallels the Alaskan coastline is relatively warm, low in salinity, and nutrient-poor (Fig.…”
Section: Distributions In Relation To Oceanographic Conditionsmentioning
confidence: 99%
“…Basin, but in many northeastern Bering Sea areas surrounding it current velocity increases of 100% or more have been measured (Fleming and Heggarty, 1966;Coachman and Tripp, 1970;Coachman et al, 1976;Schumacher and Tripp, 1979;Cacchione and Drake, 1982). Even under moderate storm conditions, wave surge currents become important at the water depths of 20-40 m encountered in northeastern Bering Sea (Cacchione and Drake, 1982).…”
Section: Current Speeds Have Not Been Measured During Storms Within Cmentioning
confidence: 99%
“…Moderate in changes in storms occur each fall in the northeastern Bering Sea resulting atmospheric pressure and wind velocity that can cause sea level set up of 1 meter and current speeds to fluctuate by as much as 100% over periods of a day or more (Coachman and Tripp, 1970;Tripp and Schumacher, 1979;Cacchione and Drake, 1982). At the northeastern edge of Chirikov Basin (Fig.…”
Section: Storm Surgesmentioning
confidence: 99%